Perceptions and Barriers of Hands Hygiene Practice among Medical Science Students in a Medical School in Malaysia - RA, Al-Naggar; K, Al-Jashamy (IIUM Medical Journal Malaysia, 2013)
Introduction: Hand hygiene is the single, most critical measure for reducing the risk of transmitting organisms to patients and health care providers. To our knowledge, none of such study on Malaysian university student exists in the literature. Therefore, the objective was to explore the perceptions and barriers of hand’s hygiene practice among university students. Methods: Focus group discussion conducted in January-2010 among 40 medical science students from Management and Science University (MSU). Simple random sampling was used, and the ethics were obtained from participants. The students were divided into five focus groups; the number of each group ranged between 8-10 members. The data obtained were classified into various categories, and the data was analyzed manually. Results: The majority of the participants mentioned that they frequently washed their hands using soap. Some of the participants washed the hands only with plain water. However, the majority of the participants mentioned that the laziness was their main barrier of frequent hand washing, followed by lack of nearby water supply and then the feeling that their hands are not dirty enough to be infected. The majority of the participants agreed that hand washing is clinically significant in reducing the spread of infectious diseases; some of them disagreed. The Majority of the participants knew the hand washing technique in the university. Conclusion: Medical science students still have some misconception and negative attitude towards hand hygiene practice. Multidisciplinary strategies needed to improve hand hygiene among students.